Urbanization And Gestion Of The Territory: The Barrinha In The XX And XXI Centuries - Costa , Maria de Lourdes Pinto Machado; Casut, Pâmela Lack (Technical and Scientific Journal Green Cities, 2022)
This article contemplates the understanding of the role played by the traditional urban sector of Rio de Janeiro - Barrinha, Largo da Barra or Barra Antiga, located in Barra da Tijuca, West Zone of the city. The main objective of the research was to evaluate the formation and differentiation of Barrinha, its particularities and identity, which makes it exemplary in the preservation of its natural and built environments in this urban microscale, and the affirmation of these residents more ancients near the active local associations. The methodology was based on the qualitative and quantitative treatment of data and information, in the approximation with the reality represented and evidented. The conclusions responded to the scope of the research developed about the course on the occupation of these spaces the formation of it’s morfology, the characteristics that marked the course of its urbanization, parallel to that verified by its growth, in the context of the neighborhood in which it is registered. Maps and photos support analysis and results. KEYWORDS: Urbanization, identity, preservation, Barrinha, Barra da Tijuca, Rio de Janeiro.